Study on atomization mechanisms and spray fragmentation characteristics of water and emulsion butachlor - Yang, Wanting; Zhong, Wei; Jia, Weidong; Ou, Mingxiong; Dong, Xiang; Zhang, Tie; Ding, Suming; Jiang, Li; Wang, Xiaowen (Frontiers in Plant Science, 2023)
Agricultural chemicals are commonly used to control pests and weeds, but that cause the problem of pesticide waste. Oil-based emulsions are often used as pesticide formulations to improve pesticides utilization. In this study, the spray visualization experiment of water and oil-based emulsion butachlor is carried out using ST flat fan nozzle at 0.1-0.5 MPa pressure. The dimensionless method is used to analyze the difference of liquid sheet fragmentation morphology and disintegration process and the influence of different fragmentation methods on droplet size. When spray liquid is water, the liquid sheet break into liquid ligaments due to the Rayleigh instability, then the ligaments break into droplets. The side view of liquid sheet is a large amplitude wave disturbance. When spray liquid is emulsion butachlor, holes are generated on the liquid sheet, then the holes break into droplets. The fragmentation method of emulsion spray is perforation mechanism. Compared with water spray, the presence of pesticide butachlor increases the droplet size, spray angle and improves the uniformity of droplet size distribution but reduce the breakup length. The spray angle shows a power law dependence of Weber number with a power of 0.17 for all conditions tested here. At 0.3 MPa, DV50 increases 25%, and Span decreases from 1.187 to 1.172. It is found that the hydrophobic components in pesticide have a significant effect on the morphology and process of atomization fragmentation. This study could provide reference for the addition of agricultural additives, the improvement of spray operation efficiency and the establishment of spray fragmentation mechanism.